Shelf break exchange events near the De Soto Canyon. (1st November 2015) - Hamilton, Peter; Speer, Kevin; Snyder, Richard; Wienders, Nicolas; Leben, Robert R.
Abstract: Observations of currents, temperature, sea-surface height, sea-surface temperature and ocean color, derived from moorings, surface and deep drifters, hydrographic surveys, and satellites, are used to characterize shelf-slope exchange events near the apex of the De Soto Canyon in the northeast Gulf of Mexico. During the winter of 2012–2013, shelf-break time series showed a number of events where cold shelf water extruded over the slope. These events were largely consistent with slope eddies of both signs influencing shelf break currents. Larger-scale circulations, derived from the Loop Current and a separating Loop Current eddy, strongly influenced circulation over the De Soto slope during summer 2012, with flow patterns consistent with potential vorticity conservation over shoaling topography. Statistical investigation into shelf-slope exchange using large numbers of surface drifters indicated that export from the shelf is larger than vice-versa, and is more uniformly distributed along the shelf break. Import onto the shelf appears to favor a region just east of the Mississippi Delta, which is also consistent with the observed onshore transport of surface oil from the Deepwater Horizon disaster. Graphical abstract: Highlights: Winter cold bottom events are observed on NE Gulf of Mexico shelf break moorings. Slope eddies mediate the export of colder shelf water. Remote deep water eddies and the Loop Current influence shelf break exchange. Western and eastern parts of the shelf break favor import and export, respectively.